2011
DOI: 10.1111/j.1464-5491.2010.03140.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic expression profiles of blood and placenta reveal significant immune‐related pathways and categories in Chinese women with gestational diabetes mellitus

Abstract: These newly identified key genes and pathways may provide valuable information about the pathogenesis of GDM and can be used to improve early diagnosis, prevention, medication design and clinical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…The mechanisms linking excess adiposity to an elevated risk of GDM are not completely understood, but recent evidence points to the role of specific hormones and cytokines known as adipokines, which are secreted by the adipose tissue [36,37]. In addition, transcriptome signatures obtained from placenta [38] and whole blood cells [39] have identified genes involved with lipid metabolism that are differentially expressed between T1D and GDM. Recently, in a meta-analysis of the transcription profiles of T1D, T2D and GDM patients, our group reported that gene expression signatures of GDM patients were closer to those of T1D patients than to T2D [40].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms linking excess adiposity to an elevated risk of GDM are not completely understood, but recent evidence points to the role of specific hormones and cytokines known as adipokines, which are secreted by the adipose tissue [36,37]. In addition, transcriptome signatures obtained from placenta [38] and whole blood cells [39] have identified genes involved with lipid metabolism that are differentially expressed between T1D and GDM. Recently, in a meta-analysis of the transcription profiles of T1D, T2D and GDM patients, our group reported that gene expression signatures of GDM patients were closer to those of T1D patients than to T2D [40].…”
Section: Introductionmentioning
confidence: 99%
“…Roles include nutrient supply to the fetus, removal from the fetus of metabolic waste and hormone production. Placental phenotypes for intrauterine growth restriction (McCarthy et al 2007, Struwe et al 2010, pre-eclampsia (Hass et al 2006, Dexlin-Mellby et al 2010 and diabetes in pregnancy (Radaelli et al 2003, Zhao et al 2011 have been described, but these have not specifically been studied in the context of maternal obesity. However, animal models have been crucial in delineating the impact of obesity on placental function.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Additionally, recent performed placental and blood transcriptome analysis in diabetic Chinese patients has shown GDM-dependent alterations in the expression of numerous immune-related genes, supporting the hypothesis of a linkage of immune system to GDM. 8 Among a panel of known immune-related genes, inducible nitric oxide (NO) synthase (iNOS), also termed as NOS2, and surfactant protein D (SP-D), a collagenous calcium-dependent lectin (or collectin), have drawn much attention as molecules not only related to inflammation but also with glucose and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%